Preclinical Evaluation of Radiation-Induced Toxicity in Targeted Alpha Therapy Using [211At] NaAt in Mice: A Revisit - Yuwei Liu; Tadashi Watabe; Kazuko Kaneda-Nakashima; Kazuhiro Ooe; Yoshifumi Shirakami; Atsushi Toyoshima; Eku Shimosegawa; Takashi Nakano; Atsushi Shinohara; Jun Hatazawa (Translational Oncology, 2020)
We recently reported the dose-dependent therapeutic effect of 211At-NaAt in differentiated thyroid cancer xenograft models. In the present study, we evaluated the radiation-induced toxicity of 211At-NaAt using detailed hematological, biochemical, and histological analyses. Biodistribution of 211At-NaAt was measured in normal ICR mice (n = 12), absorbed doses in the major organs were calculated. Groups of ICR mice (n = 60) were injected with 0.1 MBq or 1 MBq of 211At-NaAt, using saline as the control group (n = 30). Body weight and food intake were followed up for 60 days. Blood cell counts and serum level of biochemical parameters were measured 3, 7, 15, 29, 60 days after injection. Histological analyses of the major organs with hematoxylin and eosin staining were performed. Biodistribution study revealed a high-absorbed dose in the thyroid gland, stomach, bladder, heart, lungs, spleen, kidneys, and testis. The 0.1 MBq group showed no abnormalities. The 1 MBq group showed decreased body weight and food intake. Histological analysis showed atrophy and fibrosis in the thyroid gland, a transient hypospermatogenesis in the testis on day 29 was found in one mouse. Hematological toxicity was mild and transient. The total cholesterol, albumin, and total protein increased with no signs of recovery, which was considered to be caused by hypothyroidism. High-dose administration of 211At-NaAt showed transient toxicity in the white blood cells and testis without severe hematological or renal toxicity, suggesting its tolerable safety as targeted alpha-therapy for differentiated thyroid cancer in the 1 MBq group.